Pengembangan Media Pembelajaran Video Animasi tentang Toleransi dan Etika Komunikasi di SMPN 52 Jakarta - Fadhilah Sabrina; Ahmad Rifqi Luthfiansyah; Muchammad Faqih; Misti Hanita; Izzatul Mardhiah; Amaliyah Amaliyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research aims to design and develop effective learning media, which is based on animated videos about the importance of tolerance and communication ethics. The method used in this research is qualitative with an R&D (Research and Development) approach. The research subjects involved three material experts, one media expert, as well as Islamic Religious Education (PAI) teachers and Counseling Guidance (BK) teachers. The results showed that the material feasibility test using the Aiken-V index obtained a value of 0.84, which indicates a very high category and means very feasible. While the results of the media feasibility test reached a value of 1, which also means very high and feasible. Thus, this video-based learning media is very feasible to use to improve students' understanding of religious tolerance and communication ethics. However, there are some evaluations related to this learning media, especially regarding the duration of the video which is considered too long. This can cause students to lose focus and interest. Therefore, it is recommended to revise the duration of the video to make it more concise and concise, so that it can increase the effectiveness of material delivery.